Targeted pathogen profiling of ancient feces reveals common enteric infections in the Rio Zape Valley, 725–920 CE - Drew Capone; David Holcomb; Amanda Lai; Tim Meade; Karl Reinhard; Joe Brown (PLoS ONE, 2025)
DNA analysis of ancient, desiccated feces – termed paleofeces – can unlock insights into the lives of ancient peoples, including through examination of the gut microbiome and identification of specific pathogens and parasites. We collected desiccated feces from the Cave of the Dead Children (La Cueva de Los Muertos Chiquitos) in the Rio Zape Valley in Mexico dated to 725–920 CE, for targeted pathogen analysis. First, we extracted DNA with methods previously optimized for paleofeces. Then, we applied highly sensitive modern molecular tools (i.e., PCR pre-amplification followed by multi-parallel qPCR) to assess the presence of 30 enteric pathogens and gut microbes. We detected ≥1 pathogen or gut microbe associated gene in each of the ten samples and a mean of 3.9 targets per sample. The targets detected included Blastocystis spp. (n = 7), atypical enteropathogenic E. coli (n = 7), Enterobius vermicularis (n = 6), Entamoeba spp. (n = 5), enterotoxigenic E. coli (n = 5), Shigella spp./enteroinvasive E. coli (n = 3), Giardia spp. (n = 2), and E. coli O157:H7 (n = 1). The protozoan pathogens we detected (i.e., Giardia spp. and Entamoeba spp.) have been previously detected in paleofeces via enzyme-linked immunoassay (ELISA), but not via PCR. This work represents the first detection of Blastocystis spp. atypical enteropathogenic E. coli, enterotoxigenic E. coli , Shigella spp./enteroinvasive E. coli , and E. coli O157:H7 in paleofeces. These results suggest that enteric infection may have been common among the Loma San Gabriel people, who lived in the Rio Zape Valley in Mexico during this period.